Diagnostic Accuracy of Color Doppler Ultrasonography for Differentiating Benign and Malignant Thyroid Nodules: Sensitivity, Specificity, and ROC-Based Evaluation Using FNAC as Reference Standard: Color Doppler Ultrasonography for Benign and Malignant Thyroid Nodules: ROC-Based Evaluation - Orakzai, Zubair Janan; Khan, Laila; Begum, Tabassum; Noureen, Sumaira; Azam, Neelofar; Sadiq, Muhammad (Pakistan Journal of Health Sciences, 2026)
Thyroid nodules are frequently encountered in clinical practice, and accurate discrimination between benign and malignant lesions remains essential to avoid unnecessary invasive procedures. Objectives: To evaluate the diagnostic accuracy of Doppler ultrasonography using fine needle aspiration cytology (FNAC) as the reference standard. Methods: This cross-sectional diagnostic accuracy study was conducted in the Department of Radiology, Medical Teaching Institution Bacha Khan Medical College and Mardan Medical Complex, Pakistan, from 18 August to 18 December 2025. A total of 83 patients underwent gray-scale and Doppler ultrasonography followed by FNAC. Doppler findings were categorized using predefined thresholds and compared with cytology. Results: The mean age was 45.1 ± 17.2 years. Malignancy was detected in 22.9% of nodules on FNAC. Doppler ultrasonography demonstrated sensitivity 100% (95% CI: 82.4–100), specificity 85.9% (95% CI: 74.6–93.3), and overall accuracy 89.2%. The ROC curve showed an AUC of 0.93 (95% CI: 0.876–0.984). Conclusions: Doppler ultrasonography is a reliable adjunct to gray-scale ultrasound for triaging thyroid nodules and guiding FNAC selection. However, cytology remains essential for confirming malignancy.